Attitudes and Perceptions of Urban African Americans of a "Dirty Bomb" Radiological Terror Event: Results of a Qualitative Study and Implications for Effective Risk Communication. (22nd January 2015) - Bass, Sarah Bauerle; Greener, Judith R.; Ruggieri, Dominique; Parvanta, Claudia; Mora, Gabriella; Wolak, Caitlin; Normile, Rebecca; Gordon, Thomas F.
Abstract: Objectives: Radiological terror presents a real threat, but little is known about how low-income, urban African Americans may respond to such threats. The aim of this study was to understand the unique challenges of this group and to explore their knowledge of what a "dirty bomb" is, their intended behaviors should one occur, and their barriers to complying with "shelter in place" recommendations. Methods: Thirty-seven 18-65-year-olds who were users of community centers in disadvantaged areas participated in 3 focus groups in Philadelphia. Results were analyzed by using the Krueger method of analyzing narrative text. Results: The responses highlighted little knowledge or concern about a dirty bomb. Lack of trust in local authorities was expressed, with participants indicating that they did not feel their needs were addressed. While shelter in place was understood, most said they would still check on family or talk with others to get the "whole truth" because the most trusted information sources were neighbors and community leaders. Conclusion: Our results indicate that a risk communication intervention for urban minorities may support desirable behaviors in the event of a dirty bomb, but successful communication will require establishing a local leader as a spokesperson to convince people of the importance of sheltering in place.( Disaster Med Public Health Preparedness . 2015;0:1-10)